Choledocholithiasis: A Literature Review - Rizky, Muhammad Ilham; Rabbani, Muhammad Afif; Madani, Ayda Fitri; Ramadhani, Dhea Asty; Maolidi, Juan; Putra, Anak Agung Gede Agung Difa Agusta Pramana; Dwiputri, Adelya Rahma (Jurnal Biologi Tropis, 2024)
leading to various complications such as cholangitis, pancreatitis, and obstructive jaundice. The prevalence of this condition ranges from 1-15% in patients with gallstones. Common symptoms include abdominal pain, indigestion, and jaundice. The objective of this study is to review the current literature on choledocholithiasis, including its definition, epidemiology, etiology, risk factors, pathophysiology, and treatment options. The study employed a narrative literature review method, collecting relevant articles from databases such as PubMed, Google Scholar, and ProQuest. The review highlights the primary mechanisms of gallstone formation, including cholesterol supersaturation and bile stasis, as well as factors like obesity, aging, and pregnancy that increase the risk of developing choledocholithiasis. Findings suggest that management of choledocholithiasis varies from non-invasive approaches, such as medical therapy, to surgical interventions like endoscopic retrograde cholangiopancreatography (ERCP) or cholecystectomy. The study concludes that early diagnosis and appropriate treatment are critical for preventing severe complications. Regular monitoring and preventive strategies are essential for patients at risk of developing choledocholithiasis.